Osteoporosis Risk Analysis in Women Residing in Selected Urban Areas - Milu Anna Laji 1 , Phale Diksha Ramesh1 , Gumi Riram1 , Sahil Chavan1 , Akash Khade1, Sharadha Rames (Institute of Medico-legal Publications Pvt Ltd, 2020)
Osteoporosis is a bone disorder with significant changes in bone biologic material and consequent bonestructural disruption, affecting millions of people around the world from diverse ethnic groups. The numberof osteoporotic fractures increases in both men and women (by more than 3-fold over the next 50 years) asa result of the ageing population particularly in Asia and Latin America.Methodology: Results: Majority of the women are in the age group of 40 to 50 years. Majority of thewomen around 38% doesn’t have any formal education. Majority of the women (20%) were home makers.Very few women completed post-graduation. Around 36% working in private institution. Around 40 %women monthly family income is 60,000-80,000. Around 40% women were in moderate risk of gettingosteoporosis and 2 women has a high risk and 29% doesn’t have any risk towards osteoporosis. None ofthe variables are associated with the risk analysis of the women anyhow age of the women is near by theassociation as the value is 0.05.Conclusion: Previous studies suggested that osteoporosis is related to age, weight, intake of corticosteroidtablets, history of fracture, history of thyroid diseases, menstrual history and Vitamin D deficiency7. The toolis prepared to assess the risk factors. And it found that majority of the women are in moderate risk